Eating and exercise fact or fiction - Newman, Carrie; CEV Multimedia (Lubbock, Texas : CEV Multimedia Ltd.)
This video helps to understand the relationship between food and exercise, compare and contast carbohydrates, fats and proteins, explain how the body uses carbohydrates, fats and proteins and distinguish between varying demands and level of exercise
Title from title screen
Executive producer, G.W. Davis ; post production, Mike Barley
Narrator : Laura Bryan
Keywords: Exercise; Carbohydrates; Foods; Nutrition; Energy resources